Penerapan model pembelajaran assurance, relevance, interest, assessment, and satisfaction untuk meningkatkan keterampilan berpikir kritis dalam pembelajaran IPS pada peserta didik kelas IV A sekolah dasar - Sandy Anggarwati; Jenny Indrastoeti Siti Poerwanti; Siti Wahyuningsih (Universitas Sebelas Maret, 2020)
Abstract. The goal of this research is to increase critical thinking skills in social science learning by applying ARIAS learning model. This study is Classroom Action Research and have two cycles. The subjects of this study were students of the 4th A students at SD Negeri 01 Papahan Karanganyar in the 2019/2020 academic year, totalling 25 students. This study uses data collection techniques in the form of interview, observation, and tests, with data analysis of content validity and triangulation. 72% of classical completeness is obtained in the 1st cycle, and the research continued in the 2nd cycle with a result of 80% classical completeness. Based on the result of the study, it can be concluded that the critical thinking skills in social science learning on 4th A students of SD Negeri 01 Papahan karanganyar in the 2019/2020 academic year can be improved through the ARIAS learning model. This research is expected to make teachers more skilled in applying the ARIAS model to improve student’s critical thinking skills